The impact of Brexit on the UK pharmaceutical supply chain: a scoping review protocol - Milne-Ives,M; Lam,C; van,Velthoven M; Meinert,E (JMIR Research Protocols, 2020)
The continuing uncertainty around Brexit has caused concern in the pharmaceutical industry and among healthcare professionals and patients. The exact consequences of Brexit on the UK pharmaceutical supply chain will depend on whether a deal is reached and what it entails, but it is likely to be affected by the withdrawal of the UK from the EU. Regulatory issues and delays in supply have the potential to seriously negatively affect the ability of UK residents to receive an adequate and timely supply of necessary medicines.